The lived experiences of becoming first-line nurse managers: A phenomenological study - Joko Gunawan; Yupin Aungsuroch; Nazliansyah; Ade Sukarna (Wolters Kluwer Medknow Publications, 2018)
Background: Designated roles of first-line nurse managers (FLNMs) are very complex, this study aimed to develop a deeper understanding of their meaningful lived experiences. Materials and Methods: This study employed a phenomenological study using semi-structured interviews with FLNMs (n = 7) at the General Hospital of Belitung, Indonesia. The data analysis was thematic. Results: Four major themes were identified from the analysis of textual data: Feeling extraordinary, the inability to do, desire to leave the unit, and influenced by work motivation. The findings of this study revealed the positive and negative experiences of becoming FLNMs. The positive experiences were related to the feeling challenged and extraordinary to deal with many roles in management and leadership. The negative experiences included personal conflict related to the desire to leave the unit, and feeling unable to manage. However, the works of FLNMs were influenced by internal and external motivation. Conclusions: This study better informs nurse executives to develop competence and performance of FLNMs, and keep their motivation by revising performance appraisal system.